Economic Accomplices to the Argentine Dictatorship : outstanding Debts. - Verbitsky, Horacio; Bohoslavsky, Juan Pablo (New York : Cambridge University Press, 2015)
This book uncovers how banks, individuals, and companies worked as economic accomplices to the oppressive Argentinian dictatorship.
Index
Keywords: Corporations -- History -- Moral and ethical aspects -- 20th century. -- Argentina; Responsibility -- Economic aspects -- History -- 20th century -- Argentina; Businesspeople -- History -- Attitudes -- 20th century. -- Argentina; Donation